Sistem Informasi Meningkatkan Kemampuan Program Diet Berbasis Webservice - Nadeak, Nurhalimah; Diana, Has; Khowarizmi, AL (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
Overweight or obesity is a health condition of a person who has excess body fat. Individuals who are overweight or obese are more susceptible to health problems such as heart disease, stroke, diabetes, certain types of cancer and gallbladder disease. In this case, the author wants to develop an application for the ability of a web service-based diet program to find out information on the right diet in the form of ideal body weight, body mass index, physical activity and food recommendations. Calculation of calories per day from food consumed and excess The diet system is designed using historical data and graph history so that it is easy to see the progress of the diet from beginning to end. So there is no need to go to a nutritionist, while the user is easy to access anywhere and anytime by the user. In addition, this system is supported by programming languages, namely PHP and HTML Database Mysql, as well as system development using the prototyping method. The output of this system is an application that can be operated online. One of the advantages of the application compared to other device operating systems is that it is relatively cheap. is open source.